2012
DOI: 10.1111/j.1743-7563.2011.01509.x
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Malaysian patients with advanced lung adenocarcinoma and unknown epidermal growth factor receptor mutation status treated with gefitinib

Abstract: In our patients with EGFR mutation unknown advanced lung adenocarcinoma treated with gefitinib, the response rate was 36.6% and the median PFS was significantly longer in female patients, never smokers and patients with stage III disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…An earlier study in Malaysian advanced lung adenocarcinoma patients with unknown EGFR mutation status reported that the response rate to gefitinib was higher in women and neversmokers compared with men and ever-smokers. 33 This is not surprising because these demographic characteristics are associated with an increased likelihood of EGFR mutation positivity. From the results of the two models that we generated, it seems that never-smokers and women are both more likely to be associated with EGFR mutation positivity.…”
Section: Association With Sex and Smokingmentioning
confidence: 99%
“…An earlier study in Malaysian advanced lung adenocarcinoma patients with unknown EGFR mutation status reported that the response rate to gefitinib was higher in women and neversmokers compared with men and ever-smokers. 33 This is not surprising because these demographic characteristics are associated with an increased likelihood of EGFR mutation positivity. From the results of the two models that we generated, it seems that never-smokers and women are both more likely to be associated with EGFR mutation positivity.…”
Section: Association With Sex and Smokingmentioning
confidence: 99%
“…Liam et al reported that 26 patients (36.6%) achieved PR whereas no patient had CR. Moreover, 26 (36.6%) and 19 (26.8%) patients had SD and PD, respectively, with gefitinib treatment ( 11 ). A small retrospective analysis also revealed a 48% PR and 13% SD in a Malaysian population treated with gefitinib ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although data exists on the use of gefitinib in Asian population, there is very limited data on the use of this drug in patients of Malaysian descent ( 11 , 12 ). Therefore, the present study was conducted to investigate the Malaysian experience with gefitinib from a single-center in EGFR mutation-positive NSCLC patients.…”
Section: Introductionmentioning
confidence: 99%
“…The Malaysian study is a retrospective analysis of patients with adenocarcinoma. 10 The tumor response rate was 37% and median progression-free survival was 6.5 months. The differences in treatment outcomes to EGFR TKI between these studies is best explained by the difference in the incidence of the EGFR mutation in each study population.…”
mentioning
confidence: 95%
“…This has limited the statistical power of using the EGFR mutation as a predictive factor in this subgroup. In contrast, the other two studies by Liam et al and Boyer et al 10,11 did not attempt to collect tumor samples. TRUST is a phase IV prospective study on the use of erlotinib in an unselected NSCLC population.…”
mentioning
confidence: 97%